Adoption of Drone Technology for the Smart Safety Mechanism of Women - Victoria Nozick (Big Data and Computing Visions)
In any other place in the world, people crave for protection during dark times (Night). Either it is man or women. Everyone is scared of being alone where dark looks like a haunting one to everyone. Where people are going MAD towards women during at that point. So, I am contributing this project to all the women who are hustling hard to get their independence and freedom. These DRONES helps them to keep secure and do all the patrol or Police work during nights.